2007
DOI: 10.1038/sj.bjc.6603783
|View full text |Cite
|
Sign up to set email alerts
|

Recent increase of breast cancer incidence among women under the age of forty

Abstract: Using data from the Geneva Cancer Registry, we found that in 2002–2004, breast cancer incidence in women aged 25–39 years increased by 46.7% per year (95% CI: 7.1–74.0, P =0.015), which surveillance or detection bias may not fully explain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
50
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(58 citation statements)
references
References 9 publications
5
50
0
3
Order By: Relevance
“…Our study is the first nationally representative population-based sample. The increase in incidence we found was considerably less than reported by Bouchardy et al and more in line with findings from Levi et al [9,10] Both previous studies indicated that detection bias may be contributing to Swiss increases although screening is seldom recommended for women less than 50 years old. Unfortunately, we were unable to investigate effects of screening on our findings because we had no information on detection methods.…”
Section: Findings In Context With the Literaturesupporting
confidence: 60%
See 1 more Smart Citation
“…Our study is the first nationally representative population-based sample. The increase in incidence we found was considerably less than reported by Bouchardy et al and more in line with findings from Levi et al [9,10] Both previous studies indicated that detection bias may be contributing to Swiss increases although screening is seldom recommended for women less than 50 years old. Unfortunately, we were unable to investigate effects of screening on our findings because we had no information on detection methods.…”
Section: Findings In Context With the Literaturesupporting
confidence: 60%
“…In contrast, an increase in the incidence of BC in younger Swiss women has been reported albeit inconsistently. Bouchardy et al found a substantial rise in BC incidence among women aged 25e39 years in Geneva, Switzerland during the period 2002-2004 [9]. However, these findings were based on a small number of cases from a single canton cancer registry (CR) and were not confirmed by data from two other Swiss CRs [10].…”
Section: Introductionmentioning
confidence: 53%
“…The incidence has also sharply increased in younger women in more recent years, mainly in industrialized countries (Bouchardy et al 2007;Parkin et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…[2] Age-adjusted incidence has increased by about 1% per year from 1940 to 1980 and continues to rise, [3] with a growing number of women below the age of 40 affected by breast cancer in recent years. [4] doi: 10.2533/chimia.2008.406 sperm counts (see Germond and coworkers in this issue [14] ) together with the observations in wild life have raised the concern that there may be a causal link between hormone-dependent cancers and exposure to endocrine disruptors but proofs are difficult to come by. A case has been made for the organochlorine, dieldrin formerly used as an insecticide.…”
Section: Breast Cancer: the Factsmentioning
confidence: 99%